Pengaruh Citra Merek Persepsi Harga dan Kualitas Produk Terhadap Minat Membeli Suzuki Ertiga Pada Masyarakat Yogyakarta - Burhan, Hata Syahidu (Atma Workshop Innovation, 2023)
The research entitled The Influence of Brand Image Perceptions of Price and Product Quality on Interest in Buying Suzuki Ertiga in Yogyakarta Society aims to identify and analyze whether brand image, price perceptions, and product quality influence the purchase of Suzuki Ertiga simultaneously and partially. The population in this study are users and former users of Suzuki Ertiga in Yogyakarta. Samples were taken from as many as 100 respondents using a purposive sampling technique, namely sampling based on certain considerations. Data analysis using multiple regression analysis. Based on the research results, the regression equation is obtained as follows: Y = 2.525+ 0.245 X1+ 0.043 X2+ 0.316X3 + e. In the hypothesis test, it was concluded that simultaneously (test F) there is influence from the independent variables brand image (X1), price perception (X2), and product quality (X3) together on the intention to buy the Suzuki Ertiga Yogyakarta car (Y). Partially (t-test) the brand image variable (X1) and product quality (X3) have a significant and significant effect on purchase intention (Y), while the price perception variable (X2) has no significant effect on purchase intention (Y)